OPTIMIZATION OF LIMITED HOME YARD SPACE AND UTILIZATIONOF HOUSEHOLD ORGANIC WASTE INTO ECOENZYME TO REDUCE CHEMICAL DEPENDENCY IN THE HOUSEHOLD ENVIRONMENT: OPTIMALISASI LAHAN PEKARANGAN SEMPIT DAN PEMANFAATAN LIMBAH RUMAH TANGGA MENJADI ECOENZYME UNTUK MENGURANGI KETERGANTUNGAN PRODUK KIMIA DILINGKUNGAN RUMAH TANGGA - Novi, Novi Mailidarni; Sulaiman; Juliawati; Jauhari; Tasliati Djafar; Syarifuddin (PT. ROCE WISDOM ACEH, 2025)
Urban households often face the dual challenges of limited yard space and increasing dependence on chemical products for plant care and cleaning purposes. Meanwhile, organic kitchen waste is often discarded without being utilized, contributing to environmental problems. This community service program aims to empower local residents, especially women and youth, to optimize the use of narrow home yards through sustainable urban farming practices and to process household organic waste into ecoenzyme. Ecoenzyme, a product of organic waste fermentation, has multiple applications such as liquid fertilizer, natural pesticide, and environmentally friendly cleaning solution. The program includes education, training, and practical workshops on ecoenzyme production and its application in small-scale gardening. By promoting the integration of waste management and sustainable agriculture at the household level, this initiative is expected to reduce chemical usage, minimize waste, and enhance community awareness on environmental sustainability. The outcomes of this activity will include improved skills, productive home gardens, and the adoption of ecoenzyme as a green solution for daily household needs.